Infestation of Cerambycidae Species on Acacia mellifera (Vahl) Benth in the Gum Belt, Sudan - Eisa, M. Ahmed (Cutting Edge Research in Biology Vol. 1, 2022)
The Acacia mellifera (Vahl) Benth, (family Mimosaceae); namely kitr in Arabic, is a multipurpose tree in Sudan. Due to insufficient study attention and the paucity of ecological knowledge, it is frequently impossible to assess the economic harm. Due to a lack of forest entomology information on some Acacia species in Sudan, including the mellifera, it is important to characterize the infestation of Acacia mellifera by the insect’s pest under study severely infesting other Acacia. The objectives of this study were to estimate the percentage of infestation by the longhorned beetles on Mellifera trees and to inspect for damage characteristics. Consequently, a field study was carried out in the Kordofan region of Sudan from May to July 2007 to evaluate infestation characteristics based on techniques for sampling insects from trees, insect damage and sign categories described by some researchers, and tree measurements that caused infestation (e.g. crown size, and diameter, tree age, and height, and diameter at breast height). The results show the presence of infestation holes in all directions of the tree trunk except the north.Infestation rates ranged from zero to 26.68% on the study sites (n =2). Need for more ecological research on the longhorned beetles was recommended from this study